The Effect of Intellectual Capital and Profitability on Financial Distress in Manufacturing Companies in The Building Construction Sub-Sector Listed on The IDX - Sidi Birran Walidain; Noni Ardian (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the effect of intellectual capital on financial distress conditions in manufacturing companies in the building construction sub-sector listed on the Indonesia Stock Exchange (IDX). Intellectual capital is an intangible asset that plays an important role in creating added value for the company. This study uses the Value Added Intellectual Coefficient (VAIC™) method to measure intellectual capital, which consists of three main components, namely human capital, structural capital, and physical capital. Financial distress is measured using the Altman Z-Score prediction model. The population of this study is all building construction sub-sector manufacturing companies listed on the IDX during the 2018-2022 period as many as 22 companies. The sample was selected using purposive sampling technique with criteria with a sample number of 13 companies. The data used is secondary data obtained from the company's annual financial statements. Data analysis was carried out using linear regression panel data with eviews data processing tool. The results of this study show that Value Added Capital Employed (VACA) and Structural Capital Value Added (STVA) have a positive and significant effect on Financial Distress, while Value Added Human Capital (VAHU) does not have a positive and significant effect on Financial Distress in manufacturing companies in the building construction sub-sector listed on the IDX.